Local expression of interleukin‐2 by B16 melanoma cells results in decreased tumour growth and long‐term tumour dormancy. Issue 3 (5th February 2013) - Gerber, Scott A.; Sorensen, Elizabeth W.; Sedlacek, Abigail L.; Lim, Joanne Y. H.; Skrombolas, Denise; Frelinger, John G.; Lord, Edith M.
Summary The tumour microenvironment is complex containing not only neoplastic cells but also a variety of host cells. The heterogeneous infiltrating immune cells include subsets of cells with opposing functions, whose activities are mediated either directly or through the cytokines they produce. Systemic delivery of cytokines such as interleukin‐2 ( IL‐2) has been used clinically to enhance anti‐tumour responses, but these molecules are generally thought to have evolved to act locally in a paracrine fashion. In this study we examined the effect of local production of IL‐2 on the growth and the immune response to B16 melanoma cells. We found that the local production of IL‐2 enhances the number of interferon‐γ‐expressing CD8 T and natural killer cells in the tumour, as well as inducing expression of vascular cell adhesion molecule 1 on tumour vessels. These responses were largely absent in interferon‐γ knockout mice. The expression of IL‐2 in the tumour microenvironment decreases tumour growth despite also enhancing Foxp3+ CD4+ regulatory T cells and anti‐inflammatory cytokines such as IL‐10. Higher levels of IL‐2 in the tumour microenvironment eliminated the progressive growth of the B16 cells in vivo, and this inhibition was dependent on the presence of either T cells or, to a lesser extent, natural killer cells. Surprisingly however, the B16 tumours were not completely eliminated but instead were controlled for an extended period of time, suggesting that a form of tumour dormancy was established.